Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2481423
|View full text |Cite
|
Sign up to set email alerts
|

Multi-touch rotation gestures

Abstract: Rotations performed with the index finger and thumb involve some of the most complex motor action among common multi-touch gestures, yet little is known about the factors affecting performance and ergonomics. This note presents results from a study where the angle, direction, diameter, and position of rotations were systematically manipulated. Subjects were asked to perform the rotations as quickly as possible without losing contact with the display, and were allowed to skip rotations that were too uncomfortab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 6 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…This was repeated 10 times, with 10 randomly selected angles within their range of roll. This roll experiment-and the pitch experiment that is described next-largely followed a procedure from previous work on rotation using multi-finger gestures [25,36].…”
Section: Rollmentioning
confidence: 99%
“…This was repeated 10 times, with 10 randomly selected angles within their range of roll. This roll experiment-and the pitch experiment that is described next-largely followed a procedure from previous work on rotation using multi-finger gestures [25,36].…”
Section: Rollmentioning
confidence: 99%
“…Another important factor for rotation is the initial orientation of targets which can affect the user's performance [8]. We therefore investigate this context in our third experiment, where users perform unimanual rotation gestures.…”
Section: Experiments 3: Object Rotation (Varying Object Orientation)mentioning
confidence: 99%
“…A common approach in user-centered gesture design is to enable the user to design gestures for specific predefined commands (Bhandari and Lim 2008;Kray et al 2010;Wobbrock et al 2009). Whilst other researchers have investigated ergonomics in gesture interaction to better understand why certain gestures are easier to perform than others (Hoggan et al 2013;Wobbrock et al 2008), with a goal to develop design recommendations for easier performable gestures.…”
Section: Ergonomics In Gesture Interaction With Grasping Handmentioning
confidence: 99%
“…interacting with the thumb on the rear of the phone. Hoggan et al (2013) investigated ergonomics for touch gestures that are executed with a "free" hand on a tablet. They found that rotation gestures with two touches are differently executed depending on their starting points.…”
Section: Ergonomics In Gesture Executionmentioning
confidence: 99%
See 1 more Smart Citation